Reversible Carbon–Carbon Bond Breaking and Spin Equilibria in Bis(pyrimidinenorcorrole). Issue 42 (6th October 2016) - Liu, Bin; Yoshida, Takuya; Li, Xiaofang; Stępień, Marcin; Shinokubo, Hiroshi; Chmielewski, Piotr J.
Abstract: Reversible homolytic dissociation of the bis(pyrimidinenorcorrole) σ‐dimer was elucidated by means of variable temperature ESR and 1 H NMR spectroscopy, mass spectrometry, and optical spectrocopy. Dehydrogenation of the σ‐dimer yielded another dimer displaying a singlet–triplet equilibrium in solution, strong NIR absorption (1570 nm), and a narrow electrochemical HOMO–LUMO gap (0.74 V). Abstract : Porphyrinoid metal complexes : Amination of the nickel(II) complex of norcorrole under mild conditions resulted in C(sp 3 )–C(sp 3 )‐linked bis(pyrimidinenorcorrole)1 which in solution exists in equilibrium with a monomeric radical (see picture). After dehydrogenation1 shows a conformation‐dependent singlet–triplet equilibrium.